Gumdrop-cake-like CuNi/C nanofibers with tunable microstructure for microwave absorbing application. Issue 8 (1st June 2020) - Wei, Yupeng; Zhong, Kangyou; Jiang, Tiantian; Zhang, Junwei; Bi, Kaiqi; Li, Linqi; Peng, Yong
Abstract: Broadband electromagnetic microwave absorbing materials with low density are highly demanded and faced with a development challenge for the critical applications into military stealth technology and electromagnetic pollution protection. Tailoring micro-structures and compositions of carbon-based multifunctional materials is a promising strategy to satisfy the expectation. Herein, we have firstly introduced nonmagnetic Cu element to tune microstructure, chemical composition of agglomerated Cu–Ni bimetallic alloys nanoparticles in gumdrop-cake-like CuNi/C nanofibers for the usage of high-quality light microwave absorbing materials, which can integrate the advantages of carbon nanofibers and CuNi nano solid solution particles. The CuNi/C nanofiber calcined at 650 °C temperature remarkably achieves a −55.1 dB strong reflection loss at 13.4 GHz frequency and a 7.5 GHz broad bandwidth (RL ≤ −10.0 dB) at 3 mm matching thickness, exhibiting a superior microwave absorption performance. This work demonstrates that introducing nonmagnetic Cu element could provide an effective way to improve the electromagnetic performance of carbon-based composites through tuning their microstructure.